INTEGRATING ETHNOMATHEMATICS AND HIGHER-ORDER THINKING SKILLS IN INTERACTIVE ANIMATION MEDIA TO FOSTER STUDENTS’ CRITICAL THINKING - Vieke Roikhatul Malikhah; Henry Suryo Bintoro; sumaji sumaji (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2026)
Higher Order Thinking Skills (HOTS) in mathematics is still relatively low in Indonesia. One of the causes is the lack of practice and habituation in working on HOTS problems. To overcome this, innovations in learning are needed that not only improve critical thinking skills but also link mathematical concepts to local culture through ethnomathematics. The purpose of this research is to develop a valid, practical, and effective HOTS and ethnomathematics based interactive animation video to improve students' critical thinking ability. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques through observation, interviews, questionnaires, and critical thinking ability tests. Participants include students, teachers, and expert validators. Effectiveness was determined by analyzing the improvement of critical thinking skills in the experimental group and comparing the posttest results with the control group using N-Gain and an independent sample t-test. The experimental group achieved an average N-Gain of 0.62, indicating a moderate improvement, and a significantly higher posttest score (86.33) than the control group (75.48), with a Sig. (2-tailed) value of 0.000 < 0.05. These results indicate that the interactive animation video media based on HOTS and ethnomathematics developed is effective in improving students' critical thinking skills. This research contributes to the development of learning media based on theory and technology, as well as offering practical insights for future innovations in mathematics education.